2016
DOI: 10.3168/jds.2015-10773
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed modification of the flavor profiles in recombined skim milk products by enriching the volatile components

Abstract: The purpose of this study was to modify the amount and composition of volatile components in bovine milk products, in an attempt to create a recombined skim milk product with full-fat milk flavor but with only 0.5% fat. The experimental plan included lipase-catalyzed hydrolysis and esterification reactions using Palatase 20000L (Novozymes, Bagsværd, Denmark). The results, measured by the methods of volatile compositional analysis and sensory evaluation, showed that the flavor profiles of the optimal recombined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Dimethyl sulphide was highest in TMR samples and dimethyl sulfone was higher in GRS and CLV samples possibly due to the presence of more digestible proteins [1]. The ester compounds, ethyl (Z)-2-butenoate (fermented, chemical, caramel), ethyl acetate (ethereal, fruity, sweet), ethyl hexanoate, ethyl octanoate (wax, sweet, apple), ethyl pentanoate (fruity, acidic, green), methyl butanoate (fruity, apple, fusel), and methyl hexanoate (fruity, pineapple, ether), were all significantly higher in pTMR samples, possibly due to the amount of ethanol available to form ethyl esters, and methanol to form methyl esters, a reaction that can occur spontaneously, or be catalyzed by esterases or lipases produced by lactic acid bacteria [82,83]. Heptanal was more closely correlated with pGRS milk samples at day nine.…”
Section: Volatile Analyses (Feed Raw and Pasteurized Milk)mentioning
confidence: 99%
“…Dimethyl sulphide was highest in TMR samples and dimethyl sulfone was higher in GRS and CLV samples possibly due to the presence of more digestible proteins [1]. The ester compounds, ethyl (Z)-2-butenoate (fermented, chemical, caramel), ethyl acetate (ethereal, fruity, sweet), ethyl hexanoate, ethyl octanoate (wax, sweet, apple), ethyl pentanoate (fruity, acidic, green), methyl butanoate (fruity, apple, fusel), and methyl hexanoate (fruity, pineapple, ether), were all significantly higher in pTMR samples, possibly due to the amount of ethanol available to form ethyl esters, and methanol to form methyl esters, a reaction that can occur spontaneously, or be catalyzed by esterases or lipases produced by lactic acid bacteria [82,83]. Heptanal was more closely correlated with pGRS milk samples at day nine.…”
Section: Volatile Analyses (Feed Raw and Pasteurized Milk)mentioning
confidence: 99%
“…The type and content of flavor compounds of the RSM, PSM, and USM were analyzed (Table 2). Based on the qualitative and quantitative analysis of GC-MS, a total of 14 volatile compounds was found in the three skim milk samples, which were identified in previous reports [19,27]. As shown in Table 2, it was observed that the types of volatile compounds had significant differences among the three samples.…”
Section: Resultsmentioning
confidence: 63%
“…In general, the acids from the hydrolysis of triacylglycerols (TAG) were the key flavor components in the milk [19,33]. Hexanoic acid and octanoic acid had oily and waxy aromas, and they were precursors for other flavor compounds, such as methyl ketones, alcohols, and esters [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, skim milk is suitable for people with hypertension or arteriosclerosis, the elderly, and people controlling their weight. Furthermore, normal people may prevent nutrition-based diseases initiated by high fat and high cholesterol levels [3,4].…”
Section: Introductionmentioning
confidence: 99%